Thank You, Angelica : The Rugrats Book of Manners - Cecile Schoberle (United States Simon Spotlight, 1999)
When Angelica decides to teach the babies etiquette in her own special way, she learns a thing or two about manners herself!
Keywords: Read Aloud -- Read Aloud